Pemanfaatan Buah Pepaya Muda Dalam Pembuatan Dendeng Giling Kambing - Meliany, Hari Purnomo, T. Dwi Wibawa Budianta (Widya Mandala Surabaya Catholic University, 2001)
Spicy dried minced goat meat in sheet form is one of the spicy dried meat type, which could be classified as intermediate moisture meat product. In order to improve the dietary fibre content of the product, a research on the utilization of young pawpaw (Carica papaya L) fruit in the production of spicy dried minced goat meat was conducted. The research results showed that the usage of 10 up to 30 % of young pawpaw fruit could increase the dietary fibre content of the spicy dried minced goat meat with the organoleptic properties still accepted by the panelists.